EVALUATE THE ROLE OF D-DIMER IN THE DEEP VENOUS THROMDOSIS DIAGNOSIS IN THE ELDERLY PATIENT WITH HIGH – AVERAGE RISK IN WELLS SCORE - Quang Đẳng, Nguyễn (Journal of Health and Aging, 2025)
Early diagnosis and in-time treatment for the patients with deep venous thrombosis (DVT) is very important because they make mortality rate and post thrombosis outcome decreased. Screening DVT in risk patients is very necessary. From 06/2015 to 06/2016, 184 elderly inpatients (≥60 age), in Thong Nhat hospital, with high – average deep venous thrombosis risk in Wells score, are quantified D-Dimer. If D-Dimer concentration > 500 ng/ml, Dopller ultrasound lower limbs, CT scan, MRI were performed to determine deep venous thrombosis. If thrombosis wasn’t found, ultrasound was done once again after the first time 7-10 days. Average age is 74 ± 10,14. Most of patients in this study had severe medical illness, in the intensive care unit and in immobility stage > 3 days, occupied the highest ratio 57,6%; then patients with active cancer and paralysis stroke patient held the ratio in turn 20,7% and 18,5%; post operation patients gained the lowest ratio 3,3%. The patients with average risk occupied the ratio 96,2%, the patients with high ratio got 3,8%. The average D-Dimer concentration in the patients with average – high deep venous thrombosis risk in Wells score in our study is 1828,99 ± 1426 ng/ml. The ratio of the patients perfomed ultrasound at the first time is 25,2%, at the second time is 8.0%, both of them are 30.4%. Average D-dimer concentration in the patients without deep venous thrombosis is 1466,27 ng/ml, in the patients with deep venous thrombosis is 2864,93 ng/ml; average D-dimer concentration in the patients without deep venous thrombosis and with thrombosis are different satistically (p <0.001). The sensitivity and specificity of D-Dimer to two times ultrasound is 80.4% and 40.8%. The positive predictive value is 23.3%. The negative predictive value is 94.4%. D-Dimer concentrations are different in levels in Wells score (p=0.001). The negative D-Dimer test helps us eliminate the deep venous thrombosis diagnosis in the elderly patients (≥ 60 years) with average – high deep venous thrombosis risk in Wells score.